Resident perspectives on local food system performance and development priorities: A pilot analysis of the local food vitality index. Issue 2 (2nd July 2020) - Rossi, Jairus; Woods, Tim; Davis, Alison
ABSTRACT: Resident interest in local food has been growing across all areas of the supply chain in the United States. To continue this surge in interest, local food system stakeholders should strengthen areas of interest and need in their communities. Without understanding these resident perspectives, however, local food system development may not be effective. To assist in elucidating resident perspectives of the food system, we have developed an assessment tool – the Local Food Vitality Index. This survey-based approach asks residents to evaluate the performance of 20 different aspects of their food system. In this paper, we use data from a pilot national survey to illustrate the analytic possibilities of our approach and illustrate strategies for incorporating these data into local food system development decisions.